Women's Operative Method of Contraception in Dr. Soetomo General Hospital Surabaya - Obsatrya, Rio; Pranadyan, Rizki (UNUSA Press, 2020)
Background: Indonesia is expected to face a Demographic surge in 2025 so that the maternal mortality rate is at risk to follow. Steady contraception is needed to control the population growth rate. Women's Operative Method Contraception (MOW) is the most effective contraceptive tool in controlling the population growth rate. The use of MOW contraception in Dr, Soetomo General Hospital Surabaya still cannot be explained. Purpose: To know the spatial distribution of Women's Operative Method of Contraception in Dr. Soetomo General Hospital Surabaya 2016 - 2019. Method: Retrospective study using medical record data, in Dr. Soetomo General Hospital Surabaya 2016 – 2019. Results: Post-deliveries MOW contraception acceptor were 23.3% in 2016 (307 of 1320 deliveries), 29.9% in 2017 (405 of 1355 deliveries), 29.2% in 2018 (432 of 1479 deliveries) and 26, 7% in 2019 (413 of 1389 deliveries). The majority of patients aged over 35 years (72.2%), multiparous (98.6%). came from Surabaya (62.9%), non-booked case-patients (82.0%), and have an overweight BMI (45.2%). There are 55.7% of postpartum MOW acceptors with concomitant diseases. Hypertension and obesity are the highest ranks of comorbidities in the MOW contraception acceptor. Conclusion: Postpartum MOW contraception acceptor in RSUD dr. Soetomo has increased every year. But further evaluation and follow up regarding increasing the percentage of postpartum MOW contraception acceptor in Dr. Soetomo General Hospital Surabaya is still very much needed.